VERMICULTURATION AND ITS DEVELOPMENT PROSPECTS - Yigitalieva Ruhshona Rustamjon qizi; Shaumarova Mukhayyo (Web of Journals Publishing, 2025)
Reclamation products such as vermicompost and vermiculture are often used as feed additives and natural fertilizers. In addition, the most common methods and technologies for their production are relatively simple and inexpensive. This is a huge advantage over existing and currently used fertilizers and organic additives.